Adapted “Break the Cycle for Avant Garde” intervention to reduce injection assisting and promoting behaviours in people who inject drugs in Tallinn, Estonia: A pre- post trial - Anneli Uusküla; Mait Raag; David M. Barnes; Susan Tross; Talu Ave; Don C. Des Jarlais (PLoS ONE, 2023)
In the context of established and emerging injection drug use epidemics, there is a need to prevent and avert injection drug use. We tested the hypothesis that an individual motivation and skills building counselling, adapted and enhanced from Hunt’s Break the Cycle intervention targeting persons currently injecting drugs would lead to reduction in injection initiation-related behaviours among PWID in Tallinn, Estonia. For this quasi-experimental study, pre-post outcome measures included self-reported promoting behaviours (speaking positively about injecting to non-injectors, injecting in front of non-injectors, offering to give a first injection) and injection initiation behaviours (assisting with or giving a first injection) during the previous 6 months. Of 214 PWID recruited, 189 were retained (88.3%) for the follow-up at 6 months. The proportion of those who had injected in front of non-PWID significantly declined from 15.9% to 8.5%, and reporting assisting with 1st injection from 6.4% to 1.06%. Of the current injectors retained in the study, 17.5% reported not injecting drugs at the follow up. The intervention adapted for the use in the setting of high prevalence of HIV and relatively low prevalence of injection assisting, tested proved to be effective and safe.